A Rocky Discontinuation of Diet Mountain Dew - Justin Durland MD; Samuel Owens Schumann MD, MSCR (SAGE Publishing, 2022)
A 62-year-old man with a past medical history of recently diagnosed type II diabetes mellitus presented for multiple episodes of nephrolithiasis after stopping Diet Mountain Dew ingestion. Stone analysis confirmed calcium oxalate stones. It was theorized that the high citrate in Diet Mountain Dew was protective against his newly recurrent nephrolithiasis. For lifestyle preference, the patient chose lemonade-flavored Crystal Light-known to be high in citrate-instead of potassium citrate 30-40 mEq supplementation. To date, the patient's nephrolithiasis has not recurred. Potassium citrate is a preventive strategy against calcium oxalate stones in patients with suspected or confirmed hypocitraturia. Citrate binds calcium, therefore, preventing the interaction between calcium and oxalate. Alternative supplementation strategies, such as citrus-flavored sodas (eg, Diet Mountain Dew), powdered drinks (eg, Crystal Light), and natural juices (eg, lemon juice), may be plausible alternatives to potassium citrate. Patient lifestyle and the risks and benefits to a particular supplemental choice must be considered for every patient.